Study and comparison of antibacterial activities of extracts of Zataria multiflora and Teucrium polium on Penibacillus alvei - REZVANNEJAD, E.; NASIRIFAR, E.; LOTFI, S.; ABDOLINASAB, M. (Journal of the Hellenic Veterinary Medical Society, 2019)
In this study, the antibacterial activity of ethanol and methanol extracts of Zataria multiflora and Teucrium polium was determined against Paenibacillus alvei by disc diffusion method. Paenibacillus alvei is one secondary bacterium for the European foulbrood disease in honey bee. Minimum inhibitory concentration and minimum bactericidal concentration were determined by using the serial dilution method. For this, Z. multiflora and T. polium are collected from different areas of Iran then they are dried and extracted in lab. The antibacterial effect of alcoholic extracts of Z. multiflora and T. polium was lower than usual standard antibiotics (P<0.01), but the ethanol and methanol extracts of Z. multiflora at a concentration of 60mg/ml, have inhibitory and lethal effects on P. alvei. Also, 100mg/ml concentrations of ethanol extract of T. polium has inhibitory and lethal effects on this bacterium. But, the no one of used concentrations of its methanol extract has inhibitory and lethal effects. Results indicated that used extracts of Z. multiflora have the higher antibacterial effects than extract of T. polium on Paenibacillus alvei. It can be concluded that regarding the high antibacterial power of Z. multiflora, it is necessity to work on how they can be used in control and treatment of bacterial honey bee diseases.